Prolegomena to a critical edition of the Chronicle of Matthew of Edessa, with a discussion of computer-aided methods used to edit the text - Andrews, T (2009)
The Chronicle of Matthew of Edessa is the primary Armenian-language historical source for the eleventh and early twelfth centuries. Matthew was a monk who lived in the ethnically mixed city of Edessa; within his Chronicle, he describes the apogee of independent Armenia, its fall to piecemeal Byzantine annexation, the subsequent loss of Byzantium's eastern territory to the newcomer Saljuq Turks, and the sectarian tension that accompanied the First Crusade. This thesis sets out the methodology adopted for the construction of a critical edition of the text, addresses the approach that Matthew took to the composition of the Chronicle, and gives the edited text of the prophecies attributed to Yovhannēs Kozeṙn and the author's prologues to Books Two and Three of the Chronicle. Chapters 2 and 3 comprise a review of the scholarship to date on the Chronicle, and a discussion of the approach taken to a critical edition of the text. The Chronicle survives in a large number of relatively recently copied manuscripts; it was therefore necessary to devise an approach to text collation and editing that takes full advantage of recent advances in computational methods of philology. I have developed a set of software tools to assist in the task of editing the Chronicle; these tools are useful for the creation of text editions in any language that can be represented through the TEI XML standard. Chapters 4–8 give an examination of the overall framework of Matthew’s Chronicle, and of his interpretation of recent history within that framework. Following a long tradition of the use of prophecy to explain Armenian history, Matthew uses two prophecies attributed to the eleventh-century clerical scholar Yovhannēs Kozeṙn, themselves extended in the twelfth century under the influence of the Apocalypse attributed to Methodius, to frame his argument that both the Byzantine emperors and the Armenian kings had abandoned their responsibility toward the Armenian people. His attitude toward recent history, and particularly toward the Latins of Outremer, may be used to demonstrate that he wrote the Chronicle no later than 1137.